Outcome after protected full weightbearing treatment in an orthopedic device in diabetic neuropathic arthropathy (Charcot arthropathy): a comparison of unilaterally and bilaterally affected patients. Issue 1 (December 2016) - Renner, Niklas; Wirth, Stephan; Osterhoff, Georg; Böni, Thomas; Berli, Martin
Abstract Background Charcot neuropathic arthropathy (CN) is a chronic, progressive, destructive, non-infectious process that most frequently affects the bone architecture of the foot in patients with sensory neuropathy. We evaluated the outcome of protected weightbearing treatment of CN in unilaterally and bilaterally affected patients and secondarily compared outcomes in protected versus unprotected weightbearing treatment. Methods Patient records and radiographs from 2002 to 2012 were retrospectively analyzed. Patients with Type 1 or Type 2 diabetes with peripheral neuropathy were included. Exclusion criteria included immunosuppressive or osteoactive medication and the presence of bone tumors. Ninety patients (101 ft), mean age 60.7 ± 10.6 years at first diagnosis of CN, were identified. Protected weightbearing treatment was achieved by total contact cast or custom-made orthosis. Ulcer, infection, CN recurrence, and amputation rates were recorded. Mean follow-up was 48 (range 1–208) months. Results Per the Eichenholtz classification, 9 ft were prodromal, 61 in stage 1 (development), 21 in stage 2 (coalescence) and 10 in stage 3 (reconstruction). Duration of protected weightbearing was 20 ± 21 weeks and 22 ± 29 weeks in patients with unilateral and bilateral CN, respectively. In bilaterally affected patients, new ulcers developed in 9/22 (41%) feet. In unilaterally affected patients, new ulcers developed in 5/66 (8%) protected weightbearing feet and 4/13 (31%) unprotected, full weightbearing feet (p  = 0.036). The ulceration rate was significantly higher in bilaterally versus unilaterally affected patients with a protected weightbearing regimen (p  = 0.004). Soft tissue infection occurred in 1/13 (8%) unprotected weightbearing feet and 1/66 (2%) protected weightbearing feet in unilaterally affected patients, and in 1/22 (4%) protected weightbearing feet of bilaterally affected patients. Recurrence and amputation rates were similar across treatment modalities. Conclusions Bilateral CN results in significantly more ulcers than unilateral CN and leads to slightly higher soft tissue infections. Protected weightbearing in an orthopedic device can reduce the risk for complications in acute CN of the foot and ankle.